Coloniality, violence, and intergenerational trauma among displaced Syrians: An interdisciplinary scoping review - Marya Rana; Eolene Boyd‐MacMillan (Mental Health Science, 2024)
Abstract Intergenerational trauma is a recognized outcome of situations of mass violence and can be transmitted through violence against children. In some communities, present‐day issues have been linked to intergenerational transmission of trauma from colonial violence and displacement. This study examined whether issues in displaced Syrian communities are being contextualized within histories of colonial violence through a public mental health framework, and surveyed the current state of the literature addressing the question: Is the colonial legacy of displaced Syrians related to instances of violence against children? This study adopted a scoping review approach. Searches on 12 medical, psychological, and sociological databases located 1024 unique results that were doubly screened down to seven partially relevant publications. An eighth publication was added through a separate gray literature search. No results fully addressed the research question; eight partially addressed it. Five results linked displacement to violence against children, two linked coloniality to displacement, and one linked colonization to violence against children. Three connecting themes were identified: colonial powers redefine cultures and identities, subsequent identity challenges arise, and unrecognized colonial underpinnings of issues preclude pathways to justice. This study began to connect contemporary issues to histories of colonial violence, but more importantly, identified a large gap in the literature, revealing an urgent need to investigate further the ways that the colonial pasts of displaced Syrian communities can inform the intergenerational transmission of trauma, and identified an emerging public mental health field at the intersection of coloniality, displacement, and intergenerational trauma.